George B. Cortelyou papers - Cortelyou, George B. (George Bruce), 1862-1940.
Correspondence, letterbooks, memoranda, diaries, subject files, printed matter, and other papers relating chiefly to Cortelyou's duties as secretary to Presidents William McKinley and Theodore Roosevelt; to his service as U.S. secretary of commerce and labor, U.S. postmaster general, and U.S. secretary of the treasury; and to his work as chairman of the Republican National Committee. Other topics include the election of 1904, the Spanish-American War, and the 1901 Pan-American Exposition, Buffalo, N.Y.
Correspondents include Alvey A. Adee, Robert Low Bacon, Albert Jeremiah Beveridge, Cornelius Newton Bliss, Edward William Bok, Charles J. Bonaparte, Nicholas Murray Butler, Joseph Gurney Cannon, Andrew Carnegie, James Sullivan Clarkson, Grover Cleveland, Charles Gates Dawes, William R. Day, Elmer Dover, Charles W. Fairbanks, John H. Finley, Moreton Frewen, Richard Watson Gilder, Marcus Alonzo Hanna, Benjamin Harrison, John Hay, Frank H. Hitchcock, Henry Cabot Lodge, William Loeb, Ida Saxton McKinley, William McKinley, James Clark McReynolds, Victor Howard Metcalf, William H. Moody, Harry S. New, Henry C. Payne, Thomas Collier Platt, Jacob A. Riis, Elihu Root, Theodore Roosevlet, Nathan Bay Scott, Leslie M. Shaw, John Sherman, Charles Emory Smith, Oscar S. Straus, and William H. Taft.
Public official and presidential secretary.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adee, Alvey A. -- 1842-1924 -- Correspondence; Bacon, Robert Low, -- 1884-1938 -- Correspondence; Beveridge, Albert Jeremiah, -- 1862-1927 -- Correspondence; Bliss, Cornelius Newton, -- 1833-1911 -- Correspondence; Bok, Edward William, -- 1863-1930 -- Correspondence; Bonaparte, Charles J. -- 1851-1921 -- Correspondence; Butler, Nicholas Murray, -- 1862-1947 -- Correspondence; Cannon, Joseph Gurney, -- 1836-1926 -- Correspondence; Carnegie, Andrew, -- 1835-1919 -- Correspondence; Clarkson, James Sullivan, -- 1842-1918 -- Correspondence; Cleveland, Grover, -- 1837-1908 -- Correspondence; Dawes, Charles Gates, -- 1865-1951 -- Correspondence; Day, William R. -- 1849-1923 -- Correspondence; Dover, Elmer, -- 1873-1940 -- Correspondence; Fairbanks, Charles W. -- 1852-1918 -- Correspondence; Finley, John H. -- 1863-1940 -- Correspondence; Frewen, Moreton, -- 1853-1924 -- Correspondence; Gilder, Richard Watson, -- 1844-1909 -- Correspondence; Hanna, Marcus Alonzo, -- 1837-1904 -- Correspondence; Harrison, Benjamin, -- 1833-1901 -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Hitchcock, Frank H. -- 1867-1935 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; Loeb, William, -- 1866-1937 -- Correspondence; McKinley, Ida Saxton, -- 1847-1907 -- Correspondence; McKinley, William, -- 1843-1901.; McKinley, William, -- 1843-1901 -- Correspondence; McReynolds, James Clark, -- 1862-1946 -- Correspondence; Metcalf, Victor Howard, -- 1853-1936 -- Correspondence; Moody, William H. -- 1853-1917 -- Correspondence; New, Harry S. -- 1858-1937 -- Correspondence; Payne, Henry C. -- 1843-1904 -- Correspondence; Platt, Thomas Collier, -- 1833-1910 -- Correspondence; Riis, Jacob A. -- 1849-1914 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Roosevelt, Theodore, -- 1858-1919.; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Scott, Nathan Bay, -- 1842-1924 -- Correspondence; Shaw, Leslie M. -- 1848-1932 -- Correspondence; Sherman, John, -- 1823-1900 -- Correspondence; Smith, Charles Emory, -- 1842-1908 -- Correspondence; Straus, Oscar S. -- 1850-1926 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; United States. -- Department of Commerce and Labor; United States. -- Department of the Treasury; United States. -- Postmaster General; Republican National Committee (U.S.); Exhibitions -- New York (State); Presidents -- United States -- Election -- 1904.; Spanish-American War, 1898.; United States -- Politics and government -- 1865-1933.; Cabinet officers; Public officials; Secretaries, Presidential